An overview of PLOS curated collection in health literacy - Rubeena Zakar; Sarosh Iqbal (PLoS ONE, 2026)
This curated collection, launched in 2022 and concluded in 2024, explores the critical role of health literacy (HL) as a determinant of health, particularly within the framework of the 2030 Agenda for Sustainable Development Goals (SDGs). Despite not being explicitly included in the SDGs, HL underpins efforts to achieve Universal Health Coverage by empowering individuals to make informed healthcare decisions. The collection encompasses 22 original articles employing diverse methodological approaches across global settings, highlighting themes such as HL’s influence on health outcomes, access to healthcare, effective interventions, and policy integration. The articles illustrate that adequate HL is essential for navigating complex healthcare landscapes, particularly for vulnerable populations disproportionately affected by low HL. Challenges associated with inadequate HL contribute to poor self-care behaviors, increased health risks, and diminished healthcare utilization. The collection emphasizes the importance of measuring HL through established tools and discusses the intersection of HL with social determinants of health. Furthermore, it addresses the need for targeted HL interventions, particularly in marginalized communities, and underscores the role of policymakers in embedding HL into public health strategies. Ultimately, this collection provides a comprehensive overview of HL’s multifaceted nature, its implications for individual and public health, and the urgent need for sustained investment in HL research and interventions. By fostering improved HL, we can enhance healthcare access, improve health outcomes, and reduce health disparities globally.